Microstructure and mechanical properties of Al2O3-ZrO2 ceramic deposited by laser direct material deposition. Issue 15 (15th October 2018) - Li, Fazhi; Zhang, Xinwang; Sui, Changyou; Wu, Jiazhu; Wei, Haiying; Zhang, Yi
Abstract: The thin-walled structures of Al2 O3 -ZrO2 ceramic were deposited using laser direct material deposition (LDMD). The effect of heat input on Al2 O3 -ZrO2 ceramics with different Al2 O3 /ZrO2 powder weight ratios were studied and the microstructures in different regions of the deposit were analyzed. For the thin-walled structure with 85 wt% Al2 O3 and 15 wt% ZrO2 (H1 ) hypoeutectic deposition, the grain growth angle increases with increasing heat input. From the frontier region to the central region, the microstructure was transformed from a columnar dendritic structure to a cellular structure. For thin-walled structure with 65 wt% Al2 O3 and 35 wt% ZrO2 (H2 ) hypoeutectic deposition, the mean thickness of the banded structure increases with increasing heat input but decreased when the heat input was 124.3 J/mm. The minimum thickness of the banded structure was 0.16 mm. The microstructure of the frontier region exhibited cellular dendritic, while the amorphous structures appeared in the central region. The maximum hardness of the thin-walled structure with H1 hypoeutectic deposit was 21.4 GPa while the maximum fracture toughness of the H2 hypoeutectic deposit was 4.61 MPa m 1/2 . The fracture toughness was found to increases as the thickness of the banded structure decreases under high heat input. The results of this research provide some basis for attaining high quality Al2 O3 -ZrO2 ceramics by laser direct material deposition.